"Being a mom = having all the feels": social support in a postpartum depression online support group. Issue 5 (20th October 2019) - Stana, Alexandru; Miller, Alanna R.
ABSTRACT: Postpartum depression represents one of the most common complications associated with childbirth, with current estimates placing its prevalence between 13% and 19% among recent mothers. Literature suggests severe implications for both mothers and children, and identifies stressful life events, poor marital relationships, lower socioeconomic status, and lack of social support as major predictors of a PPD diagnosis. This study sought to investigate types of social support sought and received by women with PPD. In contrast with previous research, informational support was found to be the most frequently used type of support, followed by emotional support and network/community support. Selective coding revealed two overarching themes in the PPD support group: social construction of motherhood, and social barriers to treatment. The study makes policy recommendations, including suggestions to facilitate women's access to health care and support both in offline and online settings.